ChemInform Abstract: Noncentrosymmetric Rare‐Earth Copper Gallium Chalcogenides RE3CuGaCh7 (RE: La—Nd; Ch: S, Se): An Unexpected Combination. Issue 40 (October 2015) - Iyer, Abishek K.; Rudyk, Brent W.; Lin, Xinsong; Singh, Harpreet; Sharma, Arzoo Z.; Wiebe, Christopher R.; Mar, Arthur
Abstract Ln3CuGaS7 and Ln3CuGaSe7 (Ln: La—Nd) are prepared by heating stoichiometric amounts of the elements (evacuated silica tubes, 1050 °C (sulfides)/900 °C (selenides), 5 d).